2016
DOI: 10.3390/rs8030170
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Contribution of Stress Factors to Improve Wheat and Maize Yield Estimations Derived from Remotely-Sensed Dry Matter Productivity

Abstract: Abstract:According to Monteith's theory, crop biomass is linearly correlated with the amount of absorbed photosynthetically active radiation (APAR) and a constant radiation use efficiency (RUE) down-regulated by stress factors such as CO 2 fertilisation, temperature and water stress. The objective was to investigate the relative importance of these stress factors in relation to regional biomass production and yield. The production efficiency model Copernicus Global Land Service-Dry Matter Productivity (CGLS-DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 102 publications
0
6
1
Order By: Relevance
“…This is in contrast to studies in other regions, where peak NDVI has been shown to capture wheat yield variability well [3,21]. In the present study, maxNDVI occurred on average on 24 [22]. The observed maxNDVI occurred on average close to winter wheat anthesis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to studies in other regions, where peak NDVI has been shown to capture wheat yield variability well [3,21]. In the present study, maxNDVI occurred on average on 24 [22]. The observed maxNDVI occurred on average close to winter wheat anthesis.…”
Section: Discussioncontrasting
confidence: 99%
“…From these results we concluded that modelling winter wheat yield based on NDVI using an empirical model is environmentally dependent. The environmental dependency of wheat yield models based on fAPAR, another vegetation index, was already demonstrated by [23,24]. In rain-fed regions with high yields in Europe, the correlations between fAPAR and yield were low, whereas in regions where yield is water-limited, high correlations between fAPAR and yield were found [23].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, remotely sensed VIs are globally available, allowing us to monitor crop yield at the field level as well as at the global level. Several studies have already demonstrated the possibility to use VIs to monitor yield at different geographical locations and at different scales i.e., from the field to global level [12][13][14][15][16][17]. One of the VIs that is often and successfully used to estimate crop yield is the Normalized Difference Vegetation Index (NDVI) [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…1) Statistical estimation model using satellite remote sensing spectral information [6], which is obtained by establishing the relationship between vegetation index and crop yield. This type of model is commonly empirical, fundamentally simple, and lack of biological basis, making them hard to be extended to other areas [7]- [9].…”
mentioning
confidence: 99%